PTK (Penelitian Tindakan Kelas) dengan Pembelajaran Berbasis Kearifan Lokal dan Penulisan Artikel Ilmiah di SDM Laigoli, Sumba - Hendro Reku Dedu (Departement of Mathematics Education, 2024)
This IbM activity aims to increase insight into local wisdom, improve skills in compiling Local Wisdom-Based PTK proposals, prepare Local Wisdom-Based PTK reports, and improve skills in writing scientific articles. The method used in this activity is participatory learning and action (PLA), including: 1). Coordinating with partners to prepare for program implementation, contacting the expert team, 2). Preparation of several training modules as activity guides, 3). Sumba local wisdom training 4). Technical training in preparing PTK proposals based on local wisdom, 5). Training in techniques for compiling PTK reports based on local wisdom, 6). Training in scientific article writing techniques, and 7). Program assistance & evaluation. The results of this activity. Is a partner who has insight into the local wisdom of Sumba, and understands that PTK can be done using. Local wisdom of Sumba as a specific PTK that suits the needs and character of students, partners have insight and skills in preparing proposals, implementing PTK in class, and preparing PTK reports based on local wisdom, partners have insight and skills in compiling scientific articles, partners have succeeded in compiling PTK reports and scientific articles that have been